Comments on the First Plenary Civil Casatory - Miranda Canales, Manuel (2008)
This is a panoramic review of the First Repealing Plenary session realised in the history of the Judicial Power of Peru. Stands out the discrepant positions of the Civil Supreme Rooms, as well as the final position of the Total Room of the Supreme Court, refered to the validity of the extrajudicial transaction in a judicial process. Likewise it is mentioned the importance of this Repealing Plenary session and its importance for the predictability of the judicial veredicts and legal security of the country